Perspektif Hukum Mengenai Penggunaan Securities Crowdfunding pada Masa Pemulihan Ekonomi Akibat Pandemi - Andini Astarianti Soemarsono; Ukhti Dyandra Sofianti (CV Rewang Rencang, 2021)
Micro, Small, Medium Enterprises (“MSMEs”) are experiencing financial difficulties to run their business due to Pandemic. Securities Crowdfunding (“SCF”) comes as the financial strengthening of MSMEs where investors and entrepreneurs will be connected through technology-based crowdfunding applications. To find out the opportunities and risks of SCF as an investment instrument and funding solution for MSMEs, this paper will analyze SCF based on Indonesia’s capital-market law and OJK-Regulation No.25/2020 concerning Securities Crowdfunding. The research studies were written descriptively with qualitative approaches obtained by juridical-normative methods. This paper concludes that the existence of SCF can be a funding solution for MSMEs and investment instruments that benefit investors.